A comparison of perceptual-cognitive skills in expert and non-expert sports officials: a systematic review and meta-analysis - Wu, Yidong; Yang, Ziqi; Wang, Rishu; Zeng, Hongtao; Zhang, Qi (Frontiers in Psychology, 2024)
The purpose of this study is to systematically compare and assess the differences in perceptual-cognitive skills between expert and non-expert sports officials, and further explore the potential differences caused by different types of sports officials, in order to provide a more comprehensive understanding of the perceptual-cognitive skills of sports officials. Relevant literature published before 31 December 2022 was searched in four English databases. Review Manager 5.4 and Stata 12.0 software were used for meta-analysis and bias test. Expert sports officials are significantly more accurate in their decision-making than non-expert sports officials, and exhibit a large amount of effect size(SMD=1.09;95%CI:0.52,1.66;P<0.05). Expert sports officials had significantly fewer number of fixations than non-expert sports officials and showed a moderate amount of effect size(SMD=-0.71;95%CI:-1.25,-0.17;P<0.05). Expert sports officials’ duration of fixation(SMD=0.23;95%CI:-0.25,0.71;P=0.35) were not significantly different from non-expert sports officials.It can be seen that there are differences in the Perceptual-cognitive skills of expert and non-expert sports officials. Accuracy can serve as an important indicator for distinguishing the perceptual-cognitive skills of expert and non-expert sports officials. Number of fixations can serve as important indicators to differentiate the perceptual-cognitive skills of monitors.